eHealth literacy in older adults with cancer - Hoogland, Aasha I. (J Geriatr Oncol, 2020)
OBJECTIVE: Recent advances in health monitoring technology have coincided with increases in the number of older adults with cancer, many of whom report difficulty using health information technology (HIT). Previous studies have identified lower electronic health (eHealth) literacy among older adults (≥65 years) compared to younger adults (<65), but studies in older adults with cancer are limited. The goal of this study was to examine age differences in eHealth literacy and use of technology devices/HIT in patients with cancer, and characterize receptivity towards using home-based HIT to communicate with the oncology care team. MATERIALS AND METHODS: Patients (n = 198) in a Radiation Oncology clinic were offered an anonymous written questionnaire assessing demographics, eHealth literacy (eHealth Literacy Scale), current use of HIT, and interest in using home-based HIT. RESULTS AND CONCLUSION: Compared to younger patients, older patients had significantly lower eHealth literacy (p < .01), and were less likely to feel confident evaluating health resources on the Internet (p < .01) or knowing how to use the health information found on the Internet to help them (p < .01) or answer health questions (p = .01). Older patients were also less likely than younger patients to have an email address (p = .04), own a smartphone (p < .01), or use the online patient portal (p = .03). Regardless of age, most patients were not opposed to using home-based HIT to communicate with their oncology care team. Future studies on HIT use in older adults with cancer should further evaluate barriers to using HIT and ways to maximize implementation and accessibility.